2014
DOI: 10.1063/1.4902093
|View full text |Cite
|
Sign up to set email alerts
|

Contributed Review: Nuclear magnetic resonance core analysis at 0.3 T

Abstract: Nuclear magnetic resonance (NMR) provides a powerful toolbox for petrophysical characterization of reservoir core plugs and fluids in the laboratory. Previously, there has been considerable focus on low field magnet technology for well log calibration. Now there is renewed interest in the study of reservoir samples using stronger magnets to complement these standard NMR measurements. Here, the capabilities of an imaging magnet with a field strength of 0.3 T (corresponding to 12.9 MHz for proton) are reviewed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 99 publications
(160 reference statements)
1
40
0
Order By: Relevance
“…It is this relationship that is exploited in the P2DRM. NMR experiments on brine-saturated core samples of many different types of sandstones and carbonates have shown consistency with the equation pair[4,20,41,42]. These experiments empirically show that for large pores, , , and the ratio , while for small pores, the experiments are consistent with the relation , hereafter…”
supporting
confidence: 58%
“…It is this relationship that is exploited in the P2DRM. NMR experiments on brine-saturated core samples of many different types of sandstones and carbonates have shown consistency with the equation pair[4,20,41,42]. These experiments empirically show that for large pores, , , and the ratio , while for small pores, the experiments are consistent with the relation , hereafter…”
supporting
confidence: 58%
“…Consequently, the industry standard for laboratory NMR core analysis has been set at an 1 H resonance frequency of  0 = 2 MHz, corresponding to a magnetic fi eld strength of B 0 = 0.05 T. The use of low fi eld also limits the infl uence of internal gradients, enabling quantitative analysis (Mitchell et al 2010). More recently researchers have been exploring the use of other fi eld strengths to assess core such as 0.3 T as reviewed by Mitchell and Fordham (2014).…”
Section: Imaging Methodsmentioning
confidence: 98%
“…The inherent signal-to-noise ratio (SNR) of the measurement is improved by increasing the fi eld strength, enabling better spectral (chemical) and spatial (image) resolution. Furthermore, nuclei with lower gyromagnetic ratios than 1 H are more readily accessed (e.g., 23 Na, 19 F, 31 P, 13 C, 2 H) for studies of molecular structure and chemical reaction monitoring (Mitchell and Fordham 2014). High-fi eld NMR also offers the advantage of shorter radio frequency (rf) probe recovery times, allowing the detection of short relaxation time components in solids.…”
Section: Imaging Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that 23 Na MRI can be used to provide direct images of the location of brine solution using 23 Na observation (Washburn and Madelin 2010;Mitchell and Fordham 2014). Of relevance to the present study, Washburn and Madelin (2010) have demonstrated a 23 Na MRI method to monitor the movement of brine into an oil-saturated Bentheimer sandstone during a spontaneous imbibition process; however, no direct information on the hydrocarbon phase can be obtained.…”
Section: Introductionmentioning
confidence: 86%